Książki z kolekcji magnackich w Wielkim Księstwie Litewskim – interdyscyplinarne opracowanie i metodologia badań - Pietrzkiewicz, Iwona (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
Contemporary research in historical book collections has recently gathered momentum, both thanks to a greater intensification of multiangled exploration (including origin-oriented studies) and the fact of its greater accessibility through international catalogue databases. The catalogues from the Grand Duchy of Lithuania, which in the past have frequently fallen prey to dispersion and scattering, serve as an example of how difficult it is to organize them in a coherent manner. The article sets out to investigate the problem of ancestral book collections as an instructive example of strengthening international and interdisciplinary cooperation in this field of work. The ancestral collections belonging to the Sapieha and the Radziwiłł families serve to show the current state of research in the area, its concepts and perspectives.